PENERAPAN QR CODE SEBAGAI KEAMANAN DATA DAN PENGGUNAANNYA UNTUK MEDIA SALING TUKAR DATA ANTAR PARTNER - Satria, Indra; Andayati, Dina; Rachmawati, Rr. Yuliana (Jurnal Jarkom, 2015)
ABSTRACTAlongwith the rapiddevelopment of information technology, especially with regard tocomputersandthe Internet, data security is acomplex issue, one of whic his the manipulation of data. One way to prevent this is to create data security system that can prevent data manipulation activities and ensure that the data is authentic. In this case, data security technology using the QR code is afairly precise effort. Application of the method QR code on asecret message is one of the solutions in the application of data security systems. This application s built using the QR code with the function of AE Sencryption algorithm that will generatea digital image file is a three-dimensional shape ofthe barcode, then th egiven key as the AES decryption key toopen the message in the QRcode. The results of this application is a data security system that displays the message, as data security efforts. With the application of QR codeis expected to help reduce the activity of data manipulation.Â Keywords : QR code, encryption function, AES, authentic.